The quality of first aid services on the basis of patients’ opinions - Szymańska, Jolanta; Dubielis, Wiesław; Horoch, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Patient satisfaction has assumed an increasing importance the evaluation of the quality of medical care. One of the methods to measure satisfaction of the health service recipient is a questionnaire survey.  Aim. The aim of the study was to evaluate the quality of first aid services on the basis of patients’ opinions, and to assess the infl uence of selected socio-demographic factors on the expressed views. Material and methods. The survey covered 132 patients of a regional hospital in south-eastern Poland who were hospitalised after having been provided with first aid by the emergency department. The respondents assessed their contact with a call taker-dispatcher, the work of a physician and other ambulance staff, the work of an ambulance crew on arrival at a hospital and the overall quality of the service they received from the moment of calling an ambulance to hospitalization. The respondents could evaluate emergency services on a three-grade scale, as good, sufficient or bad. The study also examined the infl uence of age, place of residence, marital status, as well as the professional and material situation of the respondents on their assessment of the quality of health care. Results. The work of an emergency department was assessed positively by about 86% of the respondents. Patients who negatively evaluated the work of a call taker-dispatcher, physician, or ambulance crew members, as well as the behaviour of an ambulance crew on arrival at a hospital, ranged from 1/5 to 1/4 of all respondents. The majority of negative opinions came from patients with low income.  Conclusions. Constant monitoring of the quality of medical services, including identification of the causes of patient dissatisfaction with services provided by emergency departments, makes it possible to immediately respond to deficiencies within the limits of available financial and organizational resources. Working towards reliable standards of health services, including a preferential approach to patients, would undoubtedly improve their evaluation of the quality of emergency services.